A Perspective Around Cephalopods and Their Parasites, and Suggestions on How to Increase Knowledge in the Field - Roumbedakis, Katina; Drábková, Marie; Tyml, Tomáš; di Cristo, Carlo (Frontiers in Physiology, 2018)
Although an increased interest in several areas of cephalopod research emerged over the last years (e.g., neurobiology, aquaculture, genetics, welfare), especially after their inclusion in the EU Directive on the use of animals for experimental purposes, studies on cephalopod parasites are still lacking. Cephalopods can be intermediate, reservoir or definitive hosts to a range of parasites with a wide variety of life cycle strategies. Here, we briefly overview the current knowledge and gaps in cephalopod parasitological research, summarizing the main parasite groups that affect these animals. We also propose some key topics for future research in cephalopod parasitology. Topics discussed include: (i) standardization of the methods for accurate parasite sampling and identification; (ii) elucidation of the life cycles and transmission pathways of the main cephalopod parasites; (iii) use of cephalopod parasite host specificity to assess population boundaries; (iv) risk evaluation of possible emergent parasites for aquaculture; (v) increase our knowledge on the poorly explored limits of life; (vi) sharing of information and samples. Addressing these topics, in our view, would allow us to better understand the complex host-parasite interactions and give insights of cephalopod life history. Last but not least, increasing our knowledge of cephalopod parasitology will also help to improve rearing and welfare of these animals in captivity.